Patients Seeking Retreatment after Community Paramedic Assessment and Treatment: Piloting a Community Paramedic Unit Program in Southwest Finland - Joonas Hänninen; Anne Kouvonen; Hilla Sumanen (MDPI AG, 2020)
Community paramedic (CP) units are becoming more popular in enhancing a person's access to the need for care assessment and treatment in acute but non-life-threatening health issues. Simultaneously CP units can reduce the strain on emergency departments (EDs) by treating patients effectively at home. The efficacy of CP units is proven in previous studies, but the details of conditions patients seek retreatment at the ED after a CP unit visit are largely unknown. This study aimed to categorize CP unit patients (n = 229) seeking retreatment after a CP unit visit and investigate links between CP unit actions and patients seeking retreatment. The study was based on a data set from a six-month CP unit pilot program in Finland. The main results show that 82% of the patients assessed and treated by the CP unit did not seek retreatment. Low back symptoms and nausea were the main problems patients presented to the ED within 96 h after the CP visit. On-call physician consultation (p = 0.335) or CP unit treatment time (p = 0.629) were not associated with the frequency of ED presentation. Further studies are needed in order to investigate which types of emergency medical missions are the most suitable for CP units. The findings of this study support the effectiveness of community paramedicine programs.